A implementação da reforma curricular e o trabalho docente no Programa Mais Educação de São Paulo - Carneiro, Lislayne (2015)
The More Education Program of São Paulo (2013), an initiative of the Municipal Government through the Municipal Department of Education, implemented the curriculum reform that depended elements to facilitate its implementation in the Municipal Education Network. An element for change was the reorganization of primary education from two to three cycles. The second cycle, the Interdisciplinary Cycle has as an instrument of pedagogical change the shared teaching and research question was to investigate the teachers' view on the quality of the implementation of the instruments of reform and improvement of the teaching process. Building the foundation for positive change teaching practice is still going on and the construction of the teaching process is being discussed through meetings of teachers of Municipal Education Network. In order to monitor the implementation of elements of the curriculum reform, planning and action through shared teaching and exploring the possibilities of renewing the practice the procedure adopted was based on the qualitative approach. Methods: documentary, bibliographic, interpretive and descriptive exploratory were used to collect the data and the interview was the procedure which allowed the gathering of information and data on the vision of teachers. The report of the analysis of the results shows the monitoring by the speeches of teachers and the evolution of the change of pedagogical work. Reprogramming of teaching and the impact that caused the curriculum reform in teaching practice to reprogram the pedagogical work is still in development, and teacher vision is still in training and also practice. The question is open because the construction of the engagement of teachers is ongoing and the test result shows the need to resume and strengthen the physical priorities, infrastructure and management to the education system enabling a cutout of the reality of implementation of the curriculum reform